Melatonin delayed senescence by modulating the contents of plant signalling molecules in postharvest okras - Shi, Liyu; Chen, Yutong; Dong, Wanqi; Li, Saisai; Chen, Wei; Yang, Zhenfeng; Cao, Shifeng (Frontiers in Plant Science, 2024)
This study examined the influence of melatonin treatment on senescence process and endogenous plant signalling molecules in postharvest okras. The results indicated that melatonin treatment delayed senescence by increasing the endogenous melatonin content through upregulation of its biosynthetic genes. In addition, the treatment increased the contents of indole-3-acetic acid (IAA) and gibberellin (GA) due to the positive modulation of their metabolic and signalling genes. Furthermore, treated okras exhibited higher levels of γ-aminobutyric acid (GABA) but lower abscisic acid (ABA) content, contributing to the delayed senescence process compared to control.Overall, the findings suggested that melatonin postponed senescence in okras fruit by positively regulating endogenous signalling molecules such as melatonin, IAA, GABA, GA, and ABA.